2014
DOI: 10.1002/jclp.22147
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition and Mentalizing in the Psychotherapy of Patients With Psychosis and Personality Disorders

Abstract: Many adults with significant forms of mental illness, including psychosis and personality disorders, experience deficits in metacognition that are reflected in a limited ability to describe and think about their own mental states and those of others. Above and beyond experiencing symptoms specific to their disorder, they may be unaware of their own emotions, unable to see their own thoughts as subjective and fallible, and struggle to form complex self-representations of themselves as unique beings in the world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
87
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 27 publications
2
87
1
2
Order By: Relevance
“…This has been demonstrated in patients with depression using cognitive-behavioral therapy, treatment with selective serotonin-reuptake inhibitors (SSRIs), and repetitive transcranial magnetic stimulation (rTMS) (Berlim et al, 2013; Ilieva, 2015; Tang et al, 2009). Similarly, the negative affect and maladaptive response to stress experienced by patients with schizophrenia and high neuroticism may be good targets for treatment with metacognitive and insight therapies (REFs) (Dimaggio and Lysaker, 2015; Hillis et al, 2015). Personality scales such as the NEO-FFI are reliable, valid and feasible in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This has been demonstrated in patients with depression using cognitive-behavioral therapy, treatment with selective serotonin-reuptake inhibitors (SSRIs), and repetitive transcranial magnetic stimulation (rTMS) (Berlim et al, 2013; Ilieva, 2015; Tang et al, 2009). Similarly, the negative affect and maladaptive response to stress experienced by patients with schizophrenia and high neuroticism may be good targets for treatment with metacognitive and insight therapies (REFs) (Dimaggio and Lysaker, 2015; Hillis et al, 2015). Personality scales such as the NEO-FFI are reliable, valid and feasible in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In tandem with these studies, research has also suggested that metacognitive‐oriented psychotherapies can be useful for persons with schizophrenia as well as several forms of PD including borderline, narcissistic, avoidant and obsessive–compulsive PD . These psychotherapies prominently include at least two related variants: metacognitive interpersonal therapy (MIT) and metacognitive reflection and insight therapy (MERIT).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] In tandem with these studies, research has also suggested that metacognitive-oriented psychotherapies can be useful for persons with schizophrenia as well as several forms of PD including borderline, narcissistic, avoidant and obsessive-compulsive PD. 35,36 These psychotherapies prominently include at least two related variants: metacognitive interpersonal therapy 35,37 (MIT) and metacognitive reflection and insight therapy 18,38 (MERIT). MIT is an integrative therapeutic approach based on a step-by-step formalized procedure 39,40 in which patients are encouraged to recall the details of interpersonal interactions and identify the relationships between thoughts, feelings and behaviours involved in these episodes, leading to a shared understanding of recurrent interpersonal schemas.…”
Section: Introductionmentioning
confidence: 99%
“…As Ronningstam (2009) notes, a narcissistic patient can present both themes of grandiosity and vulnerability, depending on the reaction, for example, to a threat to self-image that may either trigger the deployment of the grandiose part as a psychological defense or may evoke insecurity and fragility in the self. Another difficulty related to narcissistic pathology is the low capacity to identify and describe one's own feelings (Dimaggio & Lysaker, 2015;Dimaggio et al, 2007;Krystal, 1998;Taylor, Bagby, & Parker, 1997). The latter is connected with emotional dysregulation and strong variations in empathic functioning in patients with pathological narcissism, which is linked with interpersonal difficulties (Ronningstam, 2016).…”
mentioning
confidence: 99%